Mathematical Modelling of Catalytic Fixed-Bed Reactor for Carbon Dioxide Reforming of Methane over Rh/Al2O3 Catalyst - Nor Aishah Saidina Amin; Istadi Istadi; New Pei Yee (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2008)
A one-dimensional mathematical model was developed to simulate the performance of catalytic fixed bed reactor for carbon dioxide reforming of methane over Rh/Al2O3 catalyst at atmospheric pressure. The reactions involved in the system are carbon dioxide reforming of methane (CORM) and reverse water gas shift reaction (RWGS). The profiles of CH4 and CO2 conversions, CO and H2 yields, molar flow rate and mole raction of all species as well as reactor temperature along the axial bed of catalyst were simulated. In addition, the effects of different reactor temperature on the reactor performance were also studied. The models can also be applied to analyze the performances of lab-scale micro reactor as well as pilot-plant scale reactor with certain modifications and model verification with experimental data. © 2008 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)